(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Mennonite pacifists did not take up arms as a matter of principle. They were originally engaged in agriculture and trade. Teaching in German was banned in schools, and the Germans began to move on. Native Jews were considered Russian subjects; merchants were allowed to trade freely throughout the region and in the largest cities of European Russia.